Determining the cutoff of rainfall for Plasmodium falciparum malaria outbreaks in India - Mercy Aparna L. Lingala; Poonam Singh; Preeti Verma; Ramesh C. Dhiman (Elsevier, 2020)
Background: Malaria outbreaks due to Plasmodium falciparum have been reported from various parts of India. Rainfall is considered as one of the major determinants for malaria outbreaks, however, an estimate of rainfall threshold for malaria is not known. Owing to the vast geographic area, the present study was planned to determine the amount of rainfall required for malaria outbreaks and the lag period between outbreak and rainfall in different Indian climatic regions. Methods: Simple statistical methods of overall mean and moving mean (case/mean ratio, CMR) were used to identify the districts with P. falciparum malaria outbreak due to rainfall and the amount of rainfall required for outbreaks. Of 120 districts reporting P. falciparum malaria outbreaks, 99 districts having substantially low number of cases (<100); <3 CMR in any year from 2009 to 2012 and districts having stable malaria transmission were excluded. Finally, analysis of outbreak month, lag period and the threshold of rainfall were determined in respect of 21 districts which represent different agro-climatic zones in the country. Whenever the moving mean of cases attained the value ≥3 in any month, that month was identified as P. falciparum malaria outbreak. The threshold amount of rainfall critical for malaria outbreak was calculated by the average mean of previous months (i.e., lag period). Results: The rainfall cutoff ranged from >70 to >600 mm in different districts. The month of outbreak varied with the climatic zones viz. arid, semi-arid, humid and per-humid districts. In humid and per-humid districts, outbreaks occurred during monsoon period whereas in arid and semi-arid regions outbreaks occurred during the post monsoon period. The lag period varied from 1-3 months; long lag period was observed in arid, semi-arid region, while short lag period in humid and per-humid regions. Conclusion: Malaria outbreaks can occur in post monsoon in arid and semi-arid region whereas in summer/monsoon in humid and per-humid regions. The lag period between rainfall and outbreak differs from one month with short lag (humid and per-humid) to long lag (arid and semi-arid). Based on the determined threshold of rainfall, the findings would be helpful in forewarning of imminent outbreak of malaria for the timely preparedness of malaria outbreaks not only in 21 studied districts, but also in several other districts of different climatic regions of India.